Coordination flexibility aided CO2-specific gating in an iron isonicotinate MOF - Singh, Himan Dev; Nandi, Shyamapada; Chakraborty, Debanjan; Singh, Kirandeep; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (Chemistry-an Asian Journal, 2022)
Coordination flexibility assisted porosity has been introduced into an Iron-isonicotinate metal-organic framework (MOF), (Fe(4-PyC)(2) . (OH). The framework showed CO2-specific gate opening behavior, which gets tuned as a function of temperature and pressure. The MOF ` s physisorptive porosity towards CO2, CH4, and N-2 was investigated; it adsorbed only CO2 via a gate opening phenomenon. The isonicotinate, representing a borderline soft base, is bound to the hard Fe3+ centre through monodentate carboxylate and pyridyl nitrogen. This moderately weak binding enables isonicotinate to spin like a spindle under the CO2 pressure opening the gate for a sharp increase in CO2 uptake at 333 mmHg (At 298 K, the CO2 uptake increases from 0.70 to 1.57 mmol/g). We investigated the MOF ` s potential for CO2/N-2 and CO2/CH4 gas separation aided by this gating. IAST model reveals that the CO2/N-2 selectivity jumps from 325 to 3131 when the gate opens, while the CO2/CH4 selectivity increases three times. Interestingly, this Fe-isonicotinate MOF did not follow the trend set by our earlier reported Hard-Soft Gate Control (established for isostructural M2+-isonicotinate MOFs (M=Mg, Mn)). However, we account for this discrepancy using the different oxidation state of metals confirmed by X-ray photoelectron spectroscopy and magnetism.
Keywords: CO2 capture; flexible MOF; gating; Isonicotinic

First-row transition metal complexes of a phosphine-silylene- based hybrid ligand - Akhtar, Ruksana; Kaulage, Sandeep H.; Sangole, Mayur P.; Tothadi, Srinu; Parvathy, Parameswaran; Parameswaran, Pattiyil; Singh, Kirandeep; Khan, Shabana (Inorganic Chemistry, 2022)
We have prepared two new silylene-phosphine-based hybrid ligands Si{N(R)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)} [R = TMS {trimethylsilyl} (1) and TBDMS {tert-butyldimethylsilyl} (2)], which possess two donor sites. Furthermore, the treatment of the bidentate ligand 1 with base metal halides {FeBr2, CoBr2, NiCl(2)middotdme [nickel chloride(II) ethylene glycol dimethyl ether]} and 2 with NiBr(2)middotdme [nickel bromide(II) ethylene glycol dimethyl ether] afforded four-coordinate six-membered metal complexes 3-6, respectively, which feature coordination from both Si(II) and P(III) sites. Subsequently, complexes 3 [(FeBr2)Si{N(SiMe3)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)}], 4 [(CoBr2)Si{N(SiMe3)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)}], 5 [(NiCl2)Si{N(SiMe3)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)}], and 6 [(NiBr2)Si{N((SiBuMe2)-Bu-t)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)}] are studied for their redox and magnetic properties with the help of UV-vis spectroscopy, cyclic voltammetry, SQUID magnetometry, and theoretical calculations. Complexes 3-6 were found to display a paramagnetic behavior. All the compounds are well established by single-crystal X-ray diffraction studies.

Intertwining of localized (d) and delocalized (π) spins in magnetically frustrated two-dimensional metal-organic frameworks - Ugale, Ajay; Ninawe, Pranay; Jain, Anil; Sangole, Mayur; Mandal, Rimpa; Singh, Kirandeep; Ballav, Nirmalya (Inorganic Chemistry, 2024)
Two-dimensional metal-organic frameworks (2D MOFs) are emerging as a new class of multifunctional materials for diversified applications, although magnetic properties have not been widely explored. The metal ions and organic ligands in some of the 2D MOFs are arranged in the well-known Kagome lattice, leading to geometric spin frustration. Hence, such systems could be the potential candidates to exhibit an exotic quantum spin liquid (QSL) state, as was observed in Cu-3(HHTP)(2) (HHTP = hexahydroxytriphenylene), with no magnetic transition down to 38 mK. Hereto, we have investigated the spin intertwining in a bimetallic 2D MOF system, M-3(HHTP)(2) (M = Cu/Zn)(,) arising from the localized (d-electron) and delocalized (pi-electron) S = 1/2 spins from the Cu(II) ions and the HHTP radicals, respectively. The origin of the spin frustration (down to 5K) was critically examined by varying the metal composition in bimetallic systems, CuxZn3-x(HHTP)(2) (x = 1, 1.5, 2), containing both S = 1/2 and S = 0 spins. Additionally, to gain a deeper understanding, we studied the spin interaction in the pristine Zn-3(HHTP)(2) system containing only S = 0 Zn(II) ions. In view of the quantitative estimate of the localized and delocalized spins, the d-pi spin correlation appears essential in understanding the unusual magnetic and/or other physical properties of such hybrid organic-inorganic 2D crystalline solids

Robust spin liquidity in 2D metal-organic framework Cu3 (HHTP)2 with S=1/2 kagome lattice - Ninawe, Pranay; Jain, Anil; Sangole, Mayur; Anas, Mohd; Ugale, Ajay; Malik, Vivek K.; Yusuf, Seikh M.; Singh, Kirandeep; Ballav, Nirmalya (Chemistry- a european journal, 2024)
On one hand electron or hole doping of quantum spin liquid (QSL) may unlock high-temperature superconductivity and on the other hand it can disrupt the spin liquidity, giving rise to a magnetically ordered ground state. Recently, a 2D MOF, Cu-3(HHTP)(2) (HHTP - 2,3,6,7,10,11-hexahydroxytriphenylene), containing Cu(II) S = 1/2 frustrated spins in the Kagome lattice is emerging as a promising QSL candidate. Herein, we present an elegant in situ redox-chemistry strategy of anchoring Cu-3(HHTP)(2) crystallites onto diamagnetic reduced graphene oxide (rGO) sheets, resulting in the formation of electron-doped Cu-3(HHTP)(2)-rGO composite which exhibited a characteristic semiconducting behavior (5 K to 300 K) with high electrical conductivity of 70 S . m(-1) and a carrier density of similar to 1.1 x 10(18) cm(-3) at 300 K. Remarkably, no magnetic transition in the Cu-3(HHTP)(2)-rGO composite was observed down to 1.5 K endorsing the robust spin liquidity of the 2D MOF Cu-3(HHTP)(2). Specific heat capacity measurements led to the estimation of the residual entropy values of 28 % and 34 % of the theoretically expected value for the pristine Cu-3(HHTP)(2) and Cu-3(HHTP)(2)-rGO composite, establishing the presence of strong quantum fluctuations down to 1.5 K (two times smaller than the value of the exchange interaction J).
Keywords: 2D Metal-organic Framework; Electron doping; Reduced graphene oxide; Spin Liquid; Spin-frustration

Tridentate NacNac tames T-shaped nickel(I) radical - Pahar, Sanjukta; Sharma, Vishal; Raj, K. Vipin; Sangole, Mayur P.; George, Christy P.; Singh, Kirandeep; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemistry- a european journal, 2024)
The reaction of a nickel(II) chloride complex containing a tridentate beta-diketiminato ligand with a picolyl group [2,6-iPr2-C6H3NC(Me)CHC(Me)NH(CH2py)]Ni(II)Cl (1)] with KSi(SiMe3)3 conveniently afforded a nickel(I) radical with a T-shaped geometry (2). The compound's metalloradical nature was confirmed through electron paramagnetic resonance (EPR) studies and its reaction with TEMPO, resulting in the formation of a highly unusual three-membered nickeloxaziridine complex (3). When reacted with disulfide and diselenide, the S-S and Se-Se bonds were cleaved, and a coupled product was formed through carbon atom of the pyridine-imine group. The nickel(I) radical activates dihydrogen at room temperature and atmospheric pressure to give the monomeric nickel hydride. A thermally stable, T-shaped, nickel(I) radical was straightforward obtained by reduction of a tridentate nacnac nickel(II) chloride with KSi(TMS)3. The metalloradical character of the compound was demonstrated by the formation of a highly unusual nickeloxaziridine complex upon addition of TEMPO. The Ni(I) species displays a rich chemistry towards activation S-S, and Se-Se bond leading to unusual C-C coupled product as well as dihydrogen activation at room temperature and atmospheric pressure to generate monomeric nickel hydride.+image
Keywords: C-C Bond formation; Hydrogen Activation; Metalloradical; Nickel; Tridentate nacnac

Unconventional hole doping of S = ½ kagome antiferromagnet CoCu3(OH)6Cl2 - Mandal, Rimpa; Ninawe, Pranay; Ananthram, K. S.; Mhase, Akash; Gupta, Kriti; Saha, Sauvik; Ugale, Ajay; Singh, Kirandeep; Tarafder, Kartick; Ballav, Nirmalya (Advanced Physics Research, 2024)
Geometrically perfect S = ½ kagome lattices with frustrated magnetism are typically electrical insulators. Electron or hole doping is predicted to induce an exotic conducting state including superconductivity. Herein, an unconventional strategy of doping an S = ½ kagome lattice CoCu3(OH)6Cl2 is adopted – a structural analogue of a well-known quantum spin liquid (QSL) candidate herbertsmithite (ZnCu3(OH)6Cl2) – by integrating it with reduced graphene oxide (rGO) via in situ redox chemistry. Such an integration drastically enhances the electrical conductivity, resulting in the transformation of an insulator to a semiconductor, corroborating the respective density of states obtained from the density functional theory calculations. Estimation of the magnetic moments, data on the Hall-effect measurements, Bader charge analysis, and photoemission signals, altogether provide a bold signature of remote hole doping in CoCu3(OH)6Cl2 by rGO. The remote doping provides an alternative to the site doping approach to impart exotic electronic properties in spin liquid candidates, specifically, the generation of topological states like Dirac metal is envisioned.

Unprecedented C-F bond cleavage in perfluoronaphthalene during cobaltocene reduction - Kundu, Gargi; Pramanik, Debjit; Dash, Soumya Ranjan; Kumar, Ravi; Sangole, Mayur; Tothadi, Srinu; Ghosh, Aryya; Vanka, Kumar; Singh, Kirandeep; Sen, Sakya S. (DALTON TRANSACTIONS, 2024)

Unveiling different structural orderings in Fe5-xGeTe2 - Walve, Vaibhav; Parakh, Piyush; Rajput, Umashankar; Mhase, Akash S.; Singh, Kirandeep; Deshpande, Aparna (Physical Review B, 2024)
We investigate the metallic van der Waals itinerant ferromagnet Fe5-xGeTe2 5 - x GeTe 2 with atomic scale, spatially resolved low-temperature scanning tunneling microscopy (STM), and spectroscopy (STS). STM images unveil / / a new structural order 2a a x 1a a along with the known order 3a a x 3a a manifesting as nonuniform domains. STS shows spatial and energy resolved local density of states that reveal the crucial influence of Fe(1) site occupancy on the system's electronic interactions. Our magnetization measurements show magnetic anomalies at lower temperatures and identify a Curie temperature (Tc) c ) surpassing room temperature. Collectively, our results elucidate the intricate nature of Fe5-xGeTe2 5 - x GeTe 2 and underscore its potential for tunability of spintronics and high-temperature magnetic applications.

Influence of ionic radius on structural, optical and multiferroic properties of RMnO3 [R= Y, Er, Yb] hexamanganites - Inchara, D. R.; Singh, Kirandeep; Sangole, Mayur; Murari, M. S.; Daivajna, Mamatha D. (Physica B-Condensed Matter, 2025)
The crystalline samples of YMnO3, ErMnO3, and YbMnO3 were synthesized by a conventional solid-state reaction technique. The single-phase hexagonal structure with the P63cm space group was verified by X-ray diffraction (XRD) study. Morphological studies show that the grains are uniform and closely packed, and that the grain size increases as the ionic radii of the rare-earth ions decrease of rare earth ions and the samples are in the stoichiometry. From the Diffused Reflectance Spectroscopy study, narrow optical band gap is observed for all the samples. Magnetic phase transitions, corresponding to the antiferromagnetic ordering, were detected for all samples. The Neel temperature was found to increase with the decrease of the ionic radii of A site element in RMnO3 (Y, Er, and Yb) samples. Ferroelectric hysteresis loops at room temperature as a function of applied electric fields reveal the leaky behaviour. The dielectric constant and dielectric loss tangent variation across different frequencies are also explored for these samples. A summary and discussion of the structural, optical, magnetic and ferroelectric properties, underlying physical mechanisms, the role of the rare earth ions, and the complex interactions in hexagonal manganites, are presented in this paper. This work emphasizes how systematic variation of A-site ionic radii influences the multiferroic properties of RMnO3, gaining thorough insights into structure-property relationships that are essential to design multifunctional materials.
Keywords: Antiferromagnetic; ferroelectric; Multiferroics; Perovskites; Photovoltaic; Recombination centers

Smallest acyclic tricationic molecule containing a Bis(phosphine)-stabilized low-valent triantimony-based Unit - Mukherjee, Nilanjana; Peerless, Benjamin; Nadurata, Vincent L.; Kumar, Vikas; Sangole, Mayur P.; Singh, Kirandeep; Wiedemann, Haakon T. A.; Kay, Christopher W. M.; Kruk, Robert; Weigend, Florian; Dehnen, Stefanie; Gonnade, Rajesh G.; et al. (Nature Communications, 2026)
Element-element bonded multiply charged cationic species are well known as dimers or small cyclic oligomers in the condensed phase. However, the smallest acyclic version, a trinuclear unit possessing greater than a monocationic charge, has remained elusive. Here we introduce a bis(phosphine) supported low valent triantimony-based tricationic compound as a new entrant in this field. Structural elucidation and electronic understanding reveal a W-shaped tricationic unit comprising of a three-center four-electron sigma-bonded triantimony moiety that is terminally capped by bis(phosphine) ligands, with the central antimony atom having two lone pairs of electrons. The unique counter trianion [Sb(O)2(OTf)4]3- (OTf = CF3SO3) possesses reactive polar Sb delta+-O delta- bonds, the structure of which is determined from single crystal X-ray diffraction analysis. The ensemble of reactive molecular fragments found in this highly charged antimony-based compound makes it thermally unstable. Nonetheless, this fully characterized fleeting species shows a diverse reactivity profile, advancing the isolation of various novel antimony compounds, including the formation of a distinct low-valent antimony-cobalt carbonyl cluster.